Cross-sectional behaviour of press-braked S690 high strength steel slender channel section stub columns under minor-axis combined loading - Zhang, Lulu (2023)
This paper reports laboratory testing and numerical modelling on the cross-sectional behaviour and resistances of press-braked S690 high strength steel slender channel section stub columns under combined compression and minor-axis bending. A testing programme, including initial geometric imperfection measurements and ten minor-axis eccentric compression tests, was firstly conducted. This was accompanied by a numerical modelling programme, including a validation study, where finite element models were developed and validated against test results, and a series of parametric studies, where the validated finite element models were used to generate further numerical data. The obtained test and numerical data were then adopted to evaluate the current codified design interaction curves for press-braked S690 high strength steel slender channel section stub columns under combined compression and minor-axis bending, as provided in the European code, North American specification and Australian/New Zealand standard. The evaluation results revealed that the codified design interaction curves led to conservative and scattered resistance predictions, mainly due to the conservative end points (i.e. the cross-section compression and bending resistances). Finally, a new design interaction curve, anchored to more accurate end points, was proposed and shown to result in a higher level of design accuracy and consistency than the codified design interaction curves.